Citizen identification system of Iraq: Challenges and barriers in enabling e-government services - Othman, Marini; Ramasamy, Ammuthavali (2013)
The e-government undertaking of Iraq has been launched since 2003 with the help of the government of Italy.One if the initiative in the undertaking is to address the pressing need of an improved identification system for its citizen.The criticality of having the system in place is expressed by having the initiative appearing at rank number two in the top ten lists of critical e-government projects.It is desired that the identification system is implemented using of a single database that reduces forgery and would allow the application to work across multiple Ministries.The transparency of this solution would achieve high levels of integrity for the government.It was estimated that the system will be completed in 2009-2010.However, at the point of this paper writing, the system is still not in place.This paper focuses on the challenges and barriers faced in the implementation of the identification system in Iraq.The challenges and barriers are identified based on the aspects of political, technology, ICTs kill, connectivity and electricity.